2020
DOI: 10.1177/0363546520964957
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Minimal Clinically Important Difference, Patient Acceptable Symptomatic State, and Substantial Clinical Benefit of the PROMIS Upper Extremity Questionnaire After Rotator Cuff Repair

Abstract: Background: The Patient-Reported Outcome Measurement Information System Upper Extremity (PROMIS UE) questionnaire has been validated as an effective and efficient outcome measure after rotator cuff repair (RCR). However, definitions of clinically significant outcomes used in interpreting this outcome measure have yet to be defined. Purpose: To define clinically significant outcomes of the PROMIS UE questionnaire in patients undergoing arthroscopic RCR. Study Design: Cohort study (diagnosis); Level of evidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
2
35
2
Order By: Relevance
“…The distribution-based MCID calculated in this study, which ranges between 3.12 and 8.65, helps to serve as an independent confirmation that our anchor-based MCID calculation falls within the proper range of expected values. 9 , 35 While the anchor-based MCID of 8.05 for PROMIS UE in TSA calculated here is larger than those previously calculated in rotator cuff repair (4.87), 17 biceps tenodesis (4.02), 13 distal radius fractures (3.6 to 4.6), 34 and nonshoulder hand and upper extremity patients (2.1), 21 it is similar in magnitude to the MCID (6.3 to 8.0) calculated for carpal tunnel release. 4 Interstudy variations such as these in the calculation of these clinical benchmark values are expected given the differences in the patient populations and calculation methods used.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The distribution-based MCID calculated in this study, which ranges between 3.12 and 8.65, helps to serve as an independent confirmation that our anchor-based MCID calculation falls within the proper range of expected values. 9 , 35 While the anchor-based MCID of 8.05 for PROMIS UE in TSA calculated here is larger than those previously calculated in rotator cuff repair (4.87), 17 biceps tenodesis (4.02), 13 distal radius fractures (3.6 to 4.6), 34 and nonshoulder hand and upper extremity patients (2.1), 21 it is similar in magnitude to the MCID (6.3 to 8.0) calculated for carpal tunnel release. 4 Interstudy variations such as these in the calculation of these clinical benchmark values are expected given the differences in the patient populations and calculation methods used.…”
Section: Discussioncontrasting
confidence: 63%
“… 29 , 35 It is therefore necessary to calculate a PROMs MCID, SCB, and PASS values in a variety of patient populations to provide clinicians with appropriate benchmarks for use in research and clinical practice. To date, there have been relatively few studies on the MCID, SCB, and PASS values for PROMIS UE in specific upper extremity orthopedic patient populations, with the available literature limited to rotator cuff repair, 17 biceps tenodesis, 13 distal radius fractures, 34 carpal tunnel release, 4 , 20 and nonshoulder hand and upper extremity patients. 21 Given the scarcity of published data in this area, the goal of our study is to calculate the MCID, SCB, and PASS for PROMIS UE in patients undergoing total shoulder arthroplasty (TSA) using both distribution- and anchor-based methods.…”
mentioning
confidence: 99%
“…All studies used self-reported PROMIS data, no studies on proxy-reported data were found. Of these 50 studies, 10 studies used only distribution-based methods [49,50,52,55,58,66,68,74,75,77]; five studies estimated a minimal important difference (MID) rather than minimal important change (MIC) [44,62,63,72,73]; one study averaged estimates based on cross-sectional and longitudinal anchors as well as distribution-based estimates [84]; one study estimated a MIC value that referred to more than a minimal important change [92]; and two studies intended to calculate an anchor-based MIC but reported only a distribution-based MIC because the area under the ROC curve was considered too low [82,83]. Data from these 19 studies were not extracted.…”
Section: Resultsmentioning
confidence: 99%
“…In 1 study of patients who underwent shoulder rotator cuff repair surgery, a question about shoulder function was used as an anchor question. 10 The answer to the question comprised up to 15 steps, and the top 3 answers (reflecting the top 20%) were considered to indicate substantial improvement. In another study of patients with shoulder biceps tenodesis, a question about postoperative pain improvement was used as an anchor question to calculate the SCB.…”
Section: Discussionmentioning
confidence: 99%
“…This cutoff value was set as a scale corresponding to the top 20% to 33% in other precedent studies with anchor questions using a scale ≥10. 10 , 27 …”
Section: Methodsmentioning
confidence: 99%